Dewatering of Water Treatment Plant Sludges Using Polystyrene and Polymethylmethacrylate - Babu, J.; Srinivasan, K. (Asian Journal of Chemistry, 2010)
The water treatment plant sludges are mainly composed of lime and alum. It cannot be dried on the sand beds because of the poor drainability of raw sludge. Chemical conditioning generally improves the sludge characteristics like specific resistance and coefficient of compressibility. The present article deals with the application of certain synthetic polymers like polystyrene (PS) and polymethylmethacrylate (PMMA) for conditioning the sludge. Their effects on sludge characteristics have been presented. The variation in the specific resistance and coefficient of compressibility have also been studied under three different sets of pH conditions.